OPTIMALISASI PARIWISATA HALAL DI INDONESIA: PERAN KEPUASAN WISATAWAN DALAM PENGEMBANGAN PARIWISATA SYARIAH YANG MAJU - Asytia Haninah (JSE: Jurnal Sharia Economica, 2025)
This study explores the development of halal tourism in Indonesia by analyzing the impact of service quality and infrastructure, with tourist satisfaction as a moderating variable. Rooted in the sharia economics discipline, the research responds to Indonesia’s untapped potential in halal tourism despite being home to the largest Muslim population. Employing a quantitative survey method, data were collected from 100 Muslim tourists who had visited halal destinations in Yogyakarta, Lombok, and Bali. Statistical analysis using SPSS and PLS-SEM confirms that infrastructure (path coefficient = 0.605) has the strongest influence on halal tourism development, followed by service quality (0.278), while tourist satisfaction has a moderate role (0.103). The findings indicate that infrastructure and service quality must be developed simultaneously to ensure sustainable growth in the halal tourism sector. The study contributes to the literature by emphasizing infrastructure’s dominant role, while acknowledging satisfaction as an important performance indicator. The results underscore the need for integrated policies focusing on sharia-compliant facilities, human resource training, and inter-sectoral collaboration. In conclusion, strengthening both physical and service infrastructure is critical to position Indonesia as a leading global halal tourism destination.